2003
DOI: 10.1086/367712
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Red Blood Cell–Complement Regulatory Proteins and Increased Levels of Circulating Immune Complexes Are Associated with Severe Malarial Anemia

Abstract: Severe anemia is one of the most lethal complications of Plasmodium falciparum malaria. Red blood cells (RBCs) from children with severe malarial anemia are deficient in complement regulatory proteins (CR1 and CD55). A case-control, age- and sex-matched study was carried out to determine whether these deficiencies are acquired or inherited and the relative contribution of these complement regulatory protein deficiencies, the immune complex level, and the parasite density to the development of severe malarial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 13 publications
(12 reference statements)
4
110
2
1
Order By: Relevance
“…Malarial anemia is multifactorial in origin; it results from the combined effects of suppression of erythropoiesis, lysis of infected erythrocytes, and the accelerated destruction of uninfected erythrocytes [21,22]. Although there are no validated predictive models of human falciparum malaria [23], the observation of malaria-associated anemia in New World monkeys with prolonged Plasmodium falciparum parasitemia has led to speculation that malaria vaccines eliciting immunity that controls but does not eliminate parasitemia might themselves increase the risk of anemia in endemic populations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Malarial anemia is multifactorial in origin; it results from the combined effects of suppression of erythropoiesis, lysis of infected erythrocytes, and the accelerated destruction of uninfected erythrocytes [21,22]. Although there are no validated predictive models of human falciparum malaria [23], the observation of malaria-associated anemia in New World monkeys with prolonged Plasmodium falciparum parasitemia has led to speculation that malaria vaccines eliciting immunity that controls but does not eliminate parasitemia might themselves increase the risk of anemia in endemic populations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Entre los mecanismos que explican la destrucción esplénica prematura de eritrocitos no parasitados, están: el daño de la membrana eritrocitaria causado por la respuesta inflamatoria, por el estrés oxidativo generado por la producción de radicales libres de oxígeno con exposición de fosfatidilserinas y por la disminución de la elasticidad de la membrana (93); el depósito de anticuerpos sobre la membrana del eritrocito que pueden estar dirigidos contra elementos modificados de la pared del glóbulo rojo y actuar como autoanticuerpos, o contra proteínas de estadios asexuales del parásito depositadas sobre la célula durante la ruptura periódica de esquizontes; y la producción de alteraciones en las proteínas reguladoras del complemento sobre la membrana del eritrocito (CR1, DAF) que pueden predisponer al depósito de complejos inmunitarios y complemento sobre el glóbulo rojo y facilitar su destrucción en el bazo (92,95,96).…”
Section: Destrucción De Eritrocitos No Parasitadosunclassified
“…Red cells are able to bind C3b-bearing ICs via CR1 and carry them to the liver and spleen where they are removed from circulation (10,11). Consequently, complement regulatory proteins may play an important role in protecting red cells from complement-mediated destruction as a result of IC formation and complement activation that occur during malaria infection (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Online address: http://www.molmed.org doi: 10.2119/2007-00093. Owuor result of IC formation and complement activation that occur during malaria infection (12)(13)(14)(15).We have shown that red cells of children with SMA have decreased levels of CR1 and CD55 (14,16,17). We hypothesized that these changes could translate into a decreased functional capacity to bind ICs and prevent complement deposition, which could result in their increased rate of destruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation